2017
DOI: 10.1186/s13063-017-1820-z
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of topical silicone gel and pressure garment therapy for burn scar prevention and management in children: study protocol for a randomised controlled trial

Abstract: BackgroundAbnormal scar development following burn injury can cause substantial physical and psychological distress to children and their families. Common burn scar prevention and management techniques include silicone therapy, pressure garment therapy, or a combination of both.Currently, no definitive, high-quality evidence is available for the effectiveness of topical silicone gel or pressure garment therapy for the prevention and management of burn scars in the paediatric population. Thus, this study aims t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 46 publications
1
16
0
1
Order By: Relevance
“…Adverse effects (type and number of effects), 20 intervention fidelity 30 (paper-based checklist designed for the study purposes), intervention burden (single items addressing intervention burden from the BBSIP, all versions), and interface pressure (Pliance X ® ; Novel Electronics, Munich, Germany) were also included. Full details for outcome measures are provided in the study protocol 31 and Supplemental Appendix 3.…”
Section: Methodsmentioning
confidence: 99%
“…Adverse effects (type and number of effects), 20 intervention fidelity 30 (paper-based checklist designed for the study purposes), intervention burden (single items addressing intervention burden from the BBSIP, all versions), and interface pressure (Pliance X ® ; Novel Electronics, Munich, Germany) were also included. Full details for outcome measures are provided in the study protocol 31 and Supplemental Appendix 3.…”
Section: Methodsmentioning
confidence: 99%
“…10 For this reason, even for burn scar, it has been reported that a topical silicone gel and pressure garment therapy also has a better VSS score for children than adults. 11 In addition, when considering the psychosocial impact of scars on one's life, it is important that more delicate scar management is needed for children than adults. Although this study was designed and surveyed by computer-based randomized selection, there were some limitations.…”
Section: Discussionmentioning
confidence: 99%
“…A single-centre, superiority, two-arm, parallel-group randomised controlled trial will be conducted to examine the effectiveness of Burnaid® hydrogel dressing as an analgesic adjunct to first aid in comparison to plastic wrap. The present study includes methods that have been modelled on successful prior trials conducted by members of this investigative team at the same participating facility as the present trial [39, 40]. The Consolidated Standards of Reporting Trials guidelines for randomised controlled trials will be followed, and the protocol adheres to the Standard Protocol Items: Recommendations for Interventional Trials guidelines (SPIRIT; see checklist in Additional file 1).…”
Section: Methodsmentioning
confidence: 99%